2008
DOI: 10.1093/qjmed/hcn107
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed thyrotoxicosis in hospitalized patients: clinical characteristics

Abstract: Weakness, weight loss and palpitations were the main symptoms in patients diagnosed with thyrotoxicosis during hospitalization. Thyrotoxicosis should be included in the differential diagnosis when patients are admitted to the hospital with those symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
6
0
3
Order By: Relevance
“…Due to these difficulties in diagnosis probably SAT in pregnant women is underestimated. In a population based study in Denmark 2.3% of new cases of hyperthyroidism was due to SAT and another study in hospitalized patients revealed SAT as etiology of thyrotoxicosis in 34.5% of patients (20,21).…”
Section: Discussionmentioning
confidence: 96%
“…Due to these difficulties in diagnosis probably SAT in pregnant women is underestimated. In a population based study in Denmark 2.3% of new cases of hyperthyroidism was due to SAT and another study in hospitalized patients revealed SAT as etiology of thyrotoxicosis in 34.5% of patients (20,21).…”
Section: Discussionmentioning
confidence: 96%
“…While in these cases the sore throat can be considered to be a direct manifestation of the underlying condition, other illnesses may be associated with sore throat due to a consequent increased predisposition to infection. This may be the case for the often cited link with thyroid disease, where 41 % of patients with newly diagnosed thyroiditis report sore throat as a first symptom [43].…”
Section: Physico-chemical Factorsmentioning
confidence: 97%
“…En relación a la causa de hospitalización, también otros estudios han encontrado una frecuencia aumentada de complicaciones cardiovasculares; especialmente, insuficiencia cardíaca y fibrilación auricular; siendo rara la enfermedad isquémica coronaria (9,11,13). Es conocido que la taquicardia sinusal es una complicación frecuente; sin embargo, la fibrilación auricular e insuficiencia cardíaca son las causas principales de muerte en pacientes hipertiroideos mayores de 50 años (19,20).…”
Section: Discussionunclassified